LIVING ARABIC MASYARAKAT TERNATE: ALTERNATIF PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA ARAB DI IAIN TERNATE - Muhammad Amri (Media Bina Ilmiah, 2023)
The development of Arabic language learning media and research at the IAIN Ternate has not optimally raised Ternate's locality values ​​related to Arabic. Ternate society, which has been in the form of a Muslim sultanate society for hundreds of years ago, strengthened by the habaib circle who has blended in as a component of Ternate society is a sign of the existence of Arabic in the life of the Ternate people. If in the realm of study of the Qur'an and Hadith there has been a proliferation of studies of the genre of living Qur'an and Hadith, then the study of living Arabic (living Arabic) in Ternate society should be of concern to Arabic language activists in Ternate with all its potential and characteristics. This study aims to explore elements of Arabic that exist and live (living Arabic) in Ternate society which can become the object of developing Arabic learning media and research at IAIN Ternate. This study is qualitative exploratory research reflecting a social phenomenon with a heuristic approach. Primary data comes from observations and reflections of researchers as the main source of heuristic studies and secondary data is taken through observation and interviews with co-researchers, then sorting and processing data is then concluded in a descriptive form.This study found several elements of Arabic that have existed and lived in the life of the people of Ternate. These elements are formulated into three categories: First, some Arabic vocabulary or terms that are absorbed and used in daily communication adapted to the local dialect; Second, the texts of the Imam's prayers which are recited after every prayer or religious event; and Third, texts of sermons and prayers of traditional sultanate mosques and local manuscript texts. The three categories above have fulfilled the full aspects of Arabic which are used in oral, reading, and written communication. Based on these three components, it can become an alternative object for the development of Arabic language learning media as well as research for the PBA IAIN Ternate Study Program.